Analisis Kinerja Protokol 6LoWPAN pada Jaringan Sensor Nirkabel dengan Topologi Jaringan Grid dan Topologi Jaringan Random Menggunakan Cooja Simulator - Andre Hadi Saputra; Primantara Hari Trisnawan; Fariz Andri Bakhtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
IPv6 over Low Power Wireless Personal Area Network (6LoWPAN), is an IPv6-based protocol that allows devices with small power consumption such as sensors to remain connected and participate in Internet of Things (IoT) with greater scalability. The presence of 6LoWPAN as an Internet protocol for wireless sensor networks that offers extensive scalability and interoperability. In this study a simulation of the use of the 6LoWPAN protocol on the Wireless Sensor Network (WSN) using Cooja simulator. After that, the analysis was carried out using the Wireshark application and the results of the Mote Output were calculated manually by reviewing the Quality of Service (QoS) parameters, such as throughput, delay and jitter to determine the performance of 6LoWPAN. Cooja Simulator is used because building a genuine propagation network is time consuming and costly. From the simulation results using grid topology and random toology that have different number of nodes and Routing Protocol for Low Power and Lossy Network (RPL). The acquisition of delay and jitter is calculated manually except throughput using the Wireshark application. The highest throughput, as well as the lowest delay and jitter, are obtained by grid network topology with the number of nodes 10 in a row which are 435 bps, 174 ms and 1,795 ms. It can be concluded that the performance of the 6LoWPAN protocol on wireless sensor networks with grid topology is better than random topologies.